The Lincoln highway - Towles, Amor (New York : Viking, 2021)
In June of 1954, 18-year-old Emmett Watson, released after serving 15 months for involuntary manslaughter, discovers that two friends from the work farm have hidden themselves in the trunk of the warden$1 (Bs car and have hatched a different plan for Emmett$1 (Bs future.s
"A novel" -- Cover.
Keywords: Brothers -- Fiction; Ex-convicts -- Fiction; Escaped prisoners -- Fiction; Railroad travel -- Fiction; Juvenile work farms -- Fiction; Escape -- Fiction; Nebraska -- Fiction; Historical fiction